Physiological Profile of Brazilian Elite Soccer Players: Comparison between U-17, U-20 and professionals - Carlos Herdy; Pablo B. Costa; Roberto Simão; James Selfe (Journal of Anthropology of Sport and Physical Education)
Possible differences in the physical values ​​related to characteristics of the age group and the play positions in soccer. The aims to analyze the isokinetic muscle strength profiles, anthropometric, neuromuscular and cardiovascular characteristics, comparing age, categories and play positions. 105 players divided into U-17, U-20, Professional and six play positions. The isokinetic test, anthropometric measurements, counter-movement jump test with arms and yo-yo intermittent recovery test were performed. Significant differences (p<0.05) were found in the professionals compared to U-20 and U-17 for body mass, height, body fat, VO2max and for U-17 in relation to professionals in the isokinetic test. Significant differences were also found between play positions (p<0.05) for body mass, height, VO2max and isokinetic. Soccer athletes playing in different positions have different profiles of physiological characteristics and U-17 have a lower level of strength compared to professionals, suggesting the importance of training specificity.